STUDI KASUS PESERTA DIDIK YANG MEMBOLOS DI KELAS VIII SMP NEGERI 19 PONTIANAK - Mita, Maria Sefania; Purwanti, Purwanti; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Case Study of Learners Who Often Skipped Class VIII in SMP Negeri 19 Pontianak. The general problem of this study is How to help students who play truant in class VIII 19 Pontianak Junior High School, The general objective of this study is to reveal the assistance efforts given to studentsin Pontianak 19 Junior High School who play truant, The theoretical benefits of this research are useful for developing the concept of science guidance and counseling, especially in individual counseling for students who often play truant in school, this research method is descriptive witha case study research form. The case subjects in this study were two people. Data collection techniques in this study were observation, interviews, documentaries and home visits. The data collection tools of this study are observation guidelines, interview guides, and reports on the results of home visits. The counseling model used to help case 1 subjects is the REBT counseling model and the counseling model used to help case 2 subjects is the Behavioral counseling model. The results of the change are that in one month the case subjects were absent. Keywords: Case Study, Students who play truant